Expression of Periostin Alternative Splicing Variants in Normal Tissue and Breast Cancer - Yuko Kanemoto; Fumihiro Sanada; Kana Shibata; Yasuo Tsunetoshi; Naruto Katsuragi; Nobutaka Koibuchi; Tetsuhiro Yoshinami; Koichi Yamamoto; Ryuichi Morishita; Yoshiaki Taniyama; Kenzo Shimazu (Biomolecules, 2024)
(1) Background: Periostin (Pn) is a secreted protein found in the extracellular matrix, and it plays a variety of roles in the human body. Physiologically, Pn has a variety of functions, including bone formation and wound healing. However, it has been implicated in the pathogenesis of various malignant tumors and chronic inflammatory diseases. Pn has alternative splicing variants (ASVs), and our previous research revealed that aberrant ASVs contribute to the pathogenesis of breast cancer and heart failure. However, the difference in expression pattern between physiologically expressed Pn-ASVs and those expressed during pathogenesis is not clear. (2) Methods and results: We examined normal and breast cancer tissues, focusing on the Pn-ASVs expression pattern to assess the significance of pathologically expressed Pn-ASVs as potential diagnostic and therapeutic targets. We found that most physiologically expressed Pn isoforms lacked exon 17 and 21. Next, we used human breast cancer and normal adjacent tissue (NAT) to investigate the expression pattern of Pn-ASVs under pathological conditions. Pn-ASVs with exon 21 were significantly increased in tumor tissues compared with NAT. In situ hybridization identified the synthesis of Pn-ASVs with exon 21 in peri-tumoral stromal cells. Additionally, the in vivo bio-distribution of 89Zr-labeled Pn antibody against exon 21 (Pn-21Ab) in mice bearing breast cancer demonstrated selective and specific accumulation in tumors, while Pn-21Ab significantly suppressed tumor growth in the mouse breast cancer model. (3) Conclusions: Together, these data indicate that Pn-ASVs might have potential for use as diagnostic and therapeutic targets for breast cancer.